Study of Histomorphological Findings in Deaths due to Heart Diseases: An Autopsy Based study - Narayan , A (Journal of Indian Academy of Forensic Medicine, 2023)
Cardiovascular diseases remain the biggest cause of death worldwide. More people die annually from cardiovascular diseases then from any other diseases. Autopsies have been diagnostic tool to establish the cause of death & the missed diagnosis, if any, in instances where there have been no clinically identified heart problems. 1 The current study is aimed to establish the morphological & histopathological changes in heart, coronaries & aorta which have contributed to cause of death & also sources as a database for frequency of heart diseases found at autopsy.